pH and Variations of Concentrations of Some Heavy Metal Infiltration Ponds at Olkaria, Kenya - Simiyu, G.M.; Tole, M. P (Africa Environmental Review Journal, 2004)
The study was carried out in the infiltration ponds at the Olkaria East geothermal power station from August 1993 to February 1994. The power station was then producing 45 megawatts and was discharging geothermal wastewater at the infiltration ponds from where it was disposed of by evaporation and seepage into the ground. The wastewaters consisted of acidic condensates (pH-9.31) and alkaline (pH. =9.31) effluents from production study was aimed at assessing the variation of pH and concentration of some heavy metals such as zinc (Zn), lead (Pb) and cadmium (cd) in geothermal wastewaters, sediments and plants Typhalatifolia, Scoenoplexus confusus and green algae. Results showed that pH reduced from 9.31 at site P IIB to 4.17 at site PIII while acidity reduced from 299 at site PlIA to 4.17 at site P III and stabilized at 7.07 at site P IV. Generally, Zn, Cd and Fb concentrations in fluids were lower than the WHO standards in drinking water (Zn = 5 Ppm, Pb = 0.05 Ppm and Cd =0.005 Ppm) However, Zn and Pb concentrations tended to increase in waters at site P IV, possibly due to evaporative concentrations. Site PIIB had the highest metal concentrations in sediments (Zn= 137.5 Ppm, Cd0.9 Ppm, Cd=0.92 ppm and Pb= 23.9 ppm). in plants, green algae had highest metal concentrations: Zn =149 ppm, Pb = 20. 03 ppm, and Cd = 0.92 ppm at sites PIV with fluid pH of7.07, while Typha latifolia had highest metal concentrations (Zn=51.0 ppm) at site P III with sediment pH= 4.3, while Pb 10.3 ppm and Cd= 0.67 ppm, at site PI with sediment pH of 3.97. Graphs of Pb/Zn ratios against pH showed that metal availability, especially Pb in waters, sediments and plants, depended on variation of pH. Therefore, management of pH is essential in the abatement of heavy metal pollution from geothermal wastewaters.